2020
DOI: 10.1101/2020.03.24.992230
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhancing the Antiviral Efficacy of RNA-Dependent RNA Polymerase Inhibition by Combination with Modulators of Pyrimidine Metabolism

Abstract: Genome-wide analysis of the mode of action of GSK983, a potent antiviral agent, led to the identification of dihydroorotate dehydrogenase (DHODH) as its target, along with the discovery that knockdown of genes in pyrimidine salvage pathways sensitized cells to GSK983. Because GSK983 is an ineffective antiviral in the presence of physiological uridine concentrations, we explored combining GSK983 with pyrimidine salvage inhibitors. We synthesized and evaluated analogs of cyclopentenyl uracil (CPU), an inhibitor … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…30,31 Recent studies have revealed that pyrimidine metabolism participates in SARS-CoV-2 infection. 32,33 In the present study, KEGG analysis results demonstrated that pyrimidine metabolism and steroid hormone biosynthesis are the major pathways involved in the host cells after SARS-CoV-2 infection. These results suggested that altered pyrimidine metabolism and steroid biosynthesis are remarkable, and perhaps druggable features after SARS-CoV-2 infection.…”
Section: The Infection Efficacy Of Sars-cov-2 Was Correlated To Acementioning
confidence: 52%
“…30,31 Recent studies have revealed that pyrimidine metabolism participates in SARS-CoV-2 infection. 32,33 In the present study, KEGG analysis results demonstrated that pyrimidine metabolism and steroid hormone biosynthesis are the major pathways involved in the host cells after SARS-CoV-2 infection. These results suggested that altered pyrimidine metabolism and steroid biosynthesis are remarkable, and perhaps druggable features after SARS-CoV-2 infection.…”
Section: The Infection Efficacy Of Sars-cov-2 Was Correlated To Acementioning
confidence: 52%